Pengenaan Pajak Terhadap Perdagangan Online di Indonesia Setelah Dibatalkannya Peraturan Menteri Keuangan (PMK) Nomor 210/PMK.010/2018 - Santoso, David (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2019)
ABSTRACT Today, trade transactions are not only done conventionally, where sellers and buyers face each other directly in a place of business to conduct trade transactions, but have transitioned to cyberspace transactions (cyber space) where trade transactions are carried out through social networks, computers, mobile phones, etc. that use an internet connection without having the seller and buyer come face to face. With the existence of a transaction, taxation appears. In the case of taxation, online trading transactions may be subject to income tax because if based on Subjective (Entrepreneur) and Objective (Income) terms in the imposition of income tax, entrepreneurs in online commerce (e-commerce) have fulfilled the requirements to be subject to income tax. In early 2019 the Ministry of Finance (MoF) issued regulations on tax payment policies for e-commerce actors in Indonesia, including content creators on social media and YouTubers. The policy was stated in Minister of Finance Regulation (PMK) Number 210 / PMK.010 / 2018 concerning Tax Treatment of Trade Transactions through Electronic Systems. However The Minister of Finance, Sri Mulyani Indrawati, withdrew Regulation of the Minister of Finance (PMK) 210 regarding the taxation treatment of trade transactions through the electronic system (e-commerce), which should come into effect April 1, 2019.That means this rule is null and void to be applied. However, prior to the existence of the Minister of Finance Regulation, there was a legal regulation ontax, ecommerce namely Law No.36 of 2008 and tax regulations related to ecommerce, which have been reaffirmed in SE-62 / PJ / 2013 concerning Affirmation of Taxation Provisions forTransactions Ecommerce and SE-06 / PJ / 2015 concerning Withholding and / or Collection of Income Taxes onTransactions ecommerce. So that sellers in the marketplace are still obliged to pay taxes. Keywords: Tax, Online Trading